Decolonial turn of collective occupations in post-apartheid South Africa: Young people's voices of occupational legacy - Mthembu, Thuli Godfrey; Julius, Whelan Gwendean; Havenga, Kristen; Mwadira, Irvin Thabang; Oliver, Kayla; Alexander, Megan (South African Journal of Occupational Therapy, 2023)
BACKGROUND: Collective occupations are a vital part of the post-apartheid South African context because they enable parents and grandparents to pass on their legacies to the young people in families and communities. However, there are social inter-generational problems such as corruption, unemployment, family conflicts and poverty that disrupt the actions of inculcating occupational legacy AIM: This study explored young people's voices of occupational legacy in a post-apartheid South African context METHOD: A socio-narratology qualitative inquiry was employed to gain insight from eight participants who were recruited using purposive sampling. Semi-structured interviews were conducted to collect data, which were analysed thematically in a credible process RESULTS: Five themes that amalgamated collective occupations with occupational legacy were identified: decoloniality of 'knowledge generation and transfer', decoloniality of 'doing', decoloniality of 'being', decoloniality of 'becoming' and decoloniality of 'belonging' CONCLUSION: The findings add to our understanding of the power of occupational legacy in ameliorating the problematic situations that enabled the young people's continuity, social change and transformation through collective occupations. It is evident in the findings that the young people exerted maximal efforts to engage in occupational decision-making activities that were guided by the available opportunities so they may transition to the different contexts.